Photochemical stability of high efficiency PTB7:PC70BM solar cell blends - Wing Chung Tsoi (Journal of Materials Chemistry A, 2014)
Thieno[3,4 b]thiophene-alt-benzodithiophene (PTB7) is a promising donor–acceptor copolymer that has achieved high efficiencies (7–9%) in organic solar cells but suffers from poor stability and degrades when exposed to light and oxygen. Using resonant Raman spectroscopy to examine the nature of this photo-oxidation, three main changes to the vibrations of the conjugated backbone are observed: (1) shift of the benzodithiophene (BDT) C[double bond, length as m-dash]C stretch peak at ∼1489 cm−1 up to ∼1499 cm−1; (2) increase in the relative intensity of coupled fused thiophene and benzene C[double bond, length as m-dash]C stretch peaks at ∼1535 and ∼1575 cm−1; (3) appearance of a new peak at ∼1650 cm−1; which suggest oxidation takes place on the BDT unit without loss of conjugation. In situ accelerated photo-degradation reveals that the observed oxidation is the initial step of degradation, which is followed by reductions in absorption and Raman scattering intensities that indicate the loss of chromophores by a second, more extensive oxidation step. Blending PTB7 with PC70BM is found to accelerate the polymer's degradation, and further shift the BDT peak to ∼1509 cm−1. Using density functional theory to simulate Raman spectra for several possible oxidised products, the initial oxidation is best described by hydroxylation of 3rd and 7th positions on the BDT donor unit.